Supplementation of Azolla microphylla Flour in Broiler Feed Increases Antibody Titers against Avian Influenza and Newcastle Disease - Ermawati, Ratna; Sirat, Muhammad Mirandy Pratama; Hartono, Madi; Fathul, Farida; Hanafi, Riyan; Fauzi, Teo Achmad (Jurnal Sain Peternakan Indonesia, 2024)
This study aimed to determine the level of protection provided by supplementation of Azolla microphylla flour in broiler feed against the antibody titers profile of Avian Influenza and Newcastle Disease. The research was conducted over two months (July-August 2021) at the broiler unit of the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. The experimental design was a Completely Randomized Design with four treatments and five replications. Each replication consisted of five Cobb CP707 strain broilers, resulting in 100 broilers. Azolla microphylla flour supplementation in the feed was administered at different doses: P0=100% commercial feed (control); P1=97.5% commercial feed + 2.5% Azolla microphylla flour; P2=95% commercial feed + 5% Azolla microphylla flour; P3=92.5% commercial feed + 7.5% Azolla microphylla flour. Serum samples were collected from 30-day-old broilers, with one sample taken from each replication, totalling 20 samples. The samples were analyzed for Avian Influenza and Newcastle Disease antibody titers at AGRILab Vaksindo Laboratory using the Hemagglutination Inhibition test. Each treatment's antibody titer data for Avian Influenza and Newcastle Disease were tabulated and presented in histograms to facilitate descriptive analysis. Antibody titers (log2 X) of Avian Influenza 4.00±0.71 and Newcastle Disease 4.60±2.07 from P2 were included in the protection level based on the WOAH Standard. The study concluded that supplementing 5% Azolla microphylla flour in broiler feed increases the antibody titers against Avian Influenza and Newcastle Disease to protective levels.